PROFILE OF INDIVIDUALS WITH NEUROLOGICAL DISORDERS ASSISTED BY A PREHOSPITAL MOBILE EMERGENCY CARE SERVICE - Sabrina Daiane Gurgel Sarmento; Rodrigo Assis Neves Dantas; Daniele Vieira Dantas; Sara Porfírio de Oliveira; Lívia Maria Nunes Henriques; Izabelle Bezerra Costa (Universidade Federal do Paraná, 2017)
This article aims to characterize the epidemiological profile of individuals with neurological disorders assisted by a prehospital mobile emergency care service. Exploratory and descriptive study with quantitative approach. Data was collected from January to June 2016, in an emergency and urgent care referral center in the state of Rio Grande do Norte. Seventy-three (73) neurological disorders were analyzed: 38 (52.1%) patients were male individuals, 43 (58.9%) were aged between 68 and 101 years. Regarding the characteristics of the neurological condition, 59 (80.8%) patients had a cerebrovascular accident (CVA), eight (11%) had seizures, three (4.1%) had low back pain related to spinal cord trauma and three (4.1%) patients had other types of neurological conditions. As for the response time to care, the average time was 31 minutes. The epidemiological profile identified was elderly men who had CVA (stroke) and whose care needs were not responded within an appropriate time.